The effectiveness of video-based multiple training modalities in community service centers for dementia: a cluster randomized controlled study - Yang, Sun-Gen; Wang, Wen-Fu; Tung, Yu-Chun; Huang, Shang-Chien; Chang, Ming-Che; Huang, Ling-Chun; Yang, Yuan-Han; Jhang, Kai-Ming (Frontiers in Medicine, 2025)
ObjectivesThis study aimed to evaluate the effectiveness of a 16-week video-based multiple training modality (MTM) program for dementia patients in Community Service Centers for Dementia (CSCDs) in Taiwan.DesignCluster Randomized controlled trial.SettingA total of 16 CSCDs across four counties in Taiwan.ParticipantsA total of 207 dementia patients and their caregivers, randomly clustered and assigned to an intervention group or a control group.InterventionThe intervention group received a 16-week video-based MTM program including dynamic physical exercises and creative activities. The control group continued with regular activities at the CSCDs.MeasurementsOutcomes measured were behavioral and psychological symptoms of dementia (BPSD) using the Neuropsychiatric Inventory Questionnaire (NPI-Q), caregiver burden using the Zarit’s Burden Interview (ZBI), and caregiver depression using the Center for Epidemiologic Studies Depression Scale (CES-D). These were assessed at baseline and post-intervention.ResultsThe intervention group showed a significant reduction in appetite/eating distress compared to the control group (change in NPI scores: −0.2 vs. 0, p = 0.026). While there was a trend toward reduced caregiver burden, the results were not statistically significant (change in ZBI scores: −3.1 vs. –1.2, p = 0.306). No significant changes were observed in overall BPSD severity or caregiver depression.ConclusionThe video-based MTM program showed potential in improving specific neuropsychological symptoms, especially appetite/eating distress, in dementia patients. The program’s ease of implementation suggests it could be expanded across CSCDs in Taiwan, with a recommendation for refinement to better support caregivers.